Pengembangan Media Video Pembelajaran Kosakata Bahasa Jepang dengan Voice Over pada Kandidat Pemagang Bidang Souzai Seizougyou di LPK Hishou Universal Style Bangli - Dea Sri Larasati, Ni Made; Suartini, Ni Nengah; Antartika, I Kadek (Japanology: The Journal of Japanese Studies, 2024)
This study is part of the third stage of Research and Development (R&D), which is to develop products and test their effectiveness. The purpose of this study was to develop a video as a Japanese language learning media focusing on vocabulary related to souzai seizougyou. In addition, this research also tested its feasibility for prospective Technical Intern Training Program (TITP) at LPK Hishou Universal Style, Bangli, Bali. There are 10 learning videos in which each video consists of vocabulary introduction, pronunciation practice, and practice questions using native speakers' voice over. This research uses the Four-D (4D) model by Thiagarajan et al. (1974) with four stages, Define, Design, Develop, and Disseminate. Data collection was carried out by interviews and expert test questionnaires (material expert test, media expert test) as well as limited product trials to produce an optimal product. As a result, the material expert obtained a score of 87.5 (very suitable) and 95.31 (very suitable) from the media expert. Furthermore, the score from the instructor trial was 100 (very suitable) and the trial with prospective apprentices was 98% (very feasible). Therefore, this learning video is suitable to be used as a media to support Japanese vocabulary learning activities.